What Matters Most to Lung Cancer Patients? A Qualitative Study in Italy and Belgium to Investigate Patient Preferences - Petrocchi, Serena; Janssens, Rosanne; Oliveri, Serena; Arnou, Reinhard; Durosini, Ilaria; Guiddi, Paolo; Louis, Evelyne; Vandevelde, Marie; Nackaerts, Kristiaan; Smith, Meredith Y.; Galli, Giulia; de Marinis, Filippo; et al. (Frontiers in Pharmacology, 2021)
Background: The potential value of patient preference studies has been recognized in the clinical individual treatment decision-making between clinicians and patients, as well as in upstream drug decision-making. Drug developers, regulators, reimbursement and Health Technology Assessment (HTA) bodies are exploring how the use of patient preference studies could inform drug development, regulatory benefit risk-assessment and reimbursement decisions respectively. Understanding patient preferences may be especially valuable in decisions regarding Non-Small Cell Lung Cancer (NSCLC) treatment options, where a variety of treatment options with different characteristics raise uncertainty about which features are most important to NSCLC patients. As part of the Innovative Medicines Initiative PREFER project, this qualitative study aimed to identify patient-relevant lung cancer treatment characteristics. Methods: This study consisted of a scoping literature review and four focus group discussions, 2 in Italy and 2 in Belgium, with a total of 24 NSCLC patients (Stages III-IV). The focus group discussions sought to identify which treatment characteristics patients find most relevant. The discussions were analyzed thematically using a thematic inductive analysis. Results: Patients highlighted themes reflecting: i) positive effects or expected gains from treatment such as greater life expectancy and maintenance of daily functioning, ii) negative effects or adverse events related to therapy that negatively impact patients’ daily functioning such as fatigue and iii) uncertainty regarding the duration and type of treatment effects. These overarching themes were consistent among patients from Belgium and Italy, suggesting that treatment aspects related to efficacy and safety as well as the psychological impact of lung cancer treatment are common areas of concern for patients, regardless of cultural background or country. Discussion: Our findings illustrate the value of using qualitative methods with patients to identify preferred treatment characteristics for advanced lung cancer. These could inform a subsequent quantitative preference survey that assesses patient trade-offs regarding treatment options.